Antibody producing capacity to the bacteriophage phi X174 in yersinia arthritis. Issue 12 (December 1987) - Bucknall, R; Leirisalo-Repo, M; Laitinen, O; Jones, J V
Abstract : Antibody production in response to the primary immunogen bacteriophage phi X174 was investigated in 14 patients with previous yersinia arthritis (YA) and in 15 controls. HLA-B27 occurred in 10 patients with YA and in three controls. After primary and secondary immunisation the antibody responses were essentially similar both in patients with YA and controls. Consequently our results suggest that antibody response to a foreign antigen does not differ between patients with YA and a normal control population. In addition, there was no difference in peak antibody responses between individuals with HLA-B27 and those without HLA-B27.